1999
DOI: 10.1095/biolreprod61.3.834
|View full text |Cite
|
Sign up to set email alerts
|

Gonadal Stage-Dependent Effects of Gonadal Steroids on Gonadotropin II Secretion in the Atlantic Croaker (Micropogonias undulatus)1

Abstract: Involvement of gonadal steroids in the control of gonadotropin II (GTH II) (homologous to LH) secretion was investigated in the Atlantic croaker (Micropogonias undulatus) using gonadectomy (Gx) and steroid replacement paradigms. Gonadectomy in males and females during the late gonadal recrudescence phase elicited significant increases in the gonadotropin response to stimulation by an LHRH analog (LHRHa), without altering basal GTH II secretion. Slow-release silicone elastomer implants of testosterone or estrad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
26
0

Year Published

2001
2001
2015
2015

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 49 publications
(30 citation statements)
references
References 43 publications
4
26
0
Order By: Relevance
“…Evidence suggests that the androgen, 5␣-androstane-3␣,17␤-diol, inhibits sexual behavior via this mechanism in rats [38]. In croaker, both GABA and androgens decrease LH secretion in fully mature females [39,40]. However, to our knowledge, competition studies to determine whether androgens and GABA bind to the same receptor in croaker brain have not been conducted.…”
Section: Discussionmentioning
confidence: 99%
“…Evidence suggests that the androgen, 5␣-androstane-3␣,17␤-diol, inhibits sexual behavior via this mechanism in rats [38]. In croaker, both GABA and androgens decrease LH secretion in fully mature females [39,40]. However, to our knowledge, competition studies to determine whether androgens and GABA bind to the same receptor in croaker brain have not been conducted.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, a very cold temperature delays vitellogenesis, the growth of oocytes as well as the spawning in the rainbow trout Oncorhynchus mykiss (Mackay and Lazier, 1993). However, the effect of high temperature is highly variable and depends on species and reproductive stage (Kagawa et al, 1983;Khan et al, 1999) as well as on different regulatory factors according to developmental stage (Van Der Kraak and Pankhurst, 1997). For instance, King et al (2003) showed that a high temperature decreases the plasma levels of oestradiol and vitellogenin in Atlantic salmon.…”
Section: Introductionmentioning
confidence: 99%
“…Other studies have indicated that the responses to GnRH vary in conjunction with the season, sexual maturity, gender, and age [31][32][33][34][35][36][37]. This would indicate that the changes in GnRH and dopamine levels to which the gonadotrophs are exposed are not sufficient for modulating the gonadotropin response.…”
Section: Introductionmentioning
confidence: 99%